Efficacy and safety of cysteamine-isobionicamide complex in postinflammatory hyperpigmentation: A 16-week, randomized, double-blinded, vehicle-controlled trial - Rosalie Tzu-Li Liu; Tsung-Fu Tsai; Yi-Jing Lai; Chau Yee Ng (Wolters Kluwer Medknow Publications, 2023)
Background: Postinflammatory hyperpigmentation (PIH) is a prevalent acquired hyperpigmentation disorder with significant psychosocial implications. Cysteamine has demonstrated notable efficacy and safety in treating hyperpigmentation disorders. This study conducted a double-blinded, randomized clinical trial to evaluate the efficacy and safety of the cysteamine-isobionicamide complex in managing PIH. Objectives: The objective was to assess the cysteamine-isobionicamide complex's efficacy for PIH treatment through comprehensive clinical and imaging evaluations. Methods: Forty patients with PIH were recruited at a tertiary medical center from 2021 to 2022 and randomized into the cysteamine-isobionicamide complex treatment group and placebo-vehicle control group. Dermatological assessments, investigator and patient global assessments, and quality of life scores were collected at baseline, week 4, week 8, and week 16. Quantitative evaluation of skin type and lesion pigmentation was performed with the Mexameter®, VISIA skin analyzer, and cellular resolution optical coherence tomography (OCT). Results: At week 8, the cysteamine-isobionicamide complex treatment group exhibited marked advancement in dermatological assessments, melasma area and severity index (MASI), total postacne hyperpigmentation index, and life quality score compared with the placebo-vehicle control group. Furthermore, melanin index and erythema index scores from Mexameter® and VISIA analysis exhibited significant improvement for brown spots at week 16. Cellular resolution OCT imaging revealed decreased melanosome capping and fewer hyperreflective melanophages. Conclusion: This study demonstrated the clinical effectiveness and safety of the cysteamine-isobionicamide complex through comprehensive dermatological assessments, imaging techniques, and patient-reported outcomes. The complex emerges as a promising therapeutic option for PIH, offering potential relief to individuals affected by this hyperpigmentation disorder.